Radiological and physicochemical properties of drinking waters consumed in the Western Black Sea Region of Turkey - Kurnaz, Aslı; Turhan, Şeref; Alzaridi, Fatma M. N. S.; Bakır, Temel Kan (Springer Science and Business Media LLC, 2021)
In this study, the average activity concentrations of 226Ra, 228Ra and 40K in drinking waters (tap and bottled) consumed in Kastamonu province of Turkey were found as 0.7, 0.5 and 1.3 Bq L−1, respectively. The average value of pH, conductivity, total dissolved solids and total hardness of waters were found as 7.5, 217 µS cm−1, 142 mg L−1 and 154 mg L−1 for tap waters and 7.4, 94 µS cm−1, 61 mg L−1 and 58 mg L−1 for bottled waters. The average activity concentration of 228Ra in drinking waters was higher than the WHO recommended concentration of 0.1 Bq L−1.
Keywords: 13. Climate action; 6. Clean water